Alliance formation: A Study of the Malaysian Automobile Supporting Industry - Ahmad Bashawir Abdul Ghani; Malcolm Tull (Gadjah Mada International Journal of Business, 2010)
Competition  in  global  industries  is  shifting  increasingly from  inter-firm  rivalry  to  rivalry  between  networks  of  firms. Strategies of individual  firms are thus contingent on the degree of interdependence that exists between them and the parent firm in the network. The present study examines the effect of network affiliation on a member firm’s decision to enter a foreign market and  international  strategic  alliance  formation.  Affiliate  firms have two options available to them: (1) enter into a competitive strategic alliance with a competitor or (2) enter into a symbioticstrategic alliance with  the parent firm of the network organiza-tion.  We tested  this assertion  using  data  from archival  sources on  sixty-five  Japanese  automobile  suppliers  that  had  set  up strategic  alliances  in  Malaysia  and  that  belonged  to  various inter-organizational  networks.  Results  indicate  that  when  affili-ate firms are dependent on the parent firm, they prefer to form symbiotic  strategic  alliances.  Conversely,  affiliate  firms  prefer competitive  strategic  alliances  with  competitors  when  they  are not  dependent  on  the  parent  firm. ALLIANCE  FORMATIONA Study of the Malaysian Automobile Supporting IndustryKeywords: automobile industry; joint venture; mode of entry; networks; strategic alliances